BRAF inhibitors: the current and the future. (August 2015) - Zhang, Weijiang
Highlights: BRAF inhibitors improved response rate and OS in BRAF V600-mutant melanoma. BRAF inhibitors are associated with cutaneous toxicity and resistance. The properties of vemurafenib and dabrafenib are compared. New therapeutic strategies to overcome resistance to BRAFi are currently under investigation. Abstract : The introduction of BRAF inhibitors (BRAFi), vemurafenib and dabrafenib, revolutionized BRAFV600-mutated metastatic melanoma treatment with improved response rate and overall survival compared to standard chemotherapy. However, the mechanism related cutaneous toxicity remains a concern. In addition, intrinsic and acquired resistance remain the key challenges in BRAFi therapy. Extensive efforts to elucidate the mechanisms have led to an improved understanding of disease biology and resulted in exploration of multiple new therapeutic options. While the future looks bright with multiple new therapeutic strategies in exploration and possible new generations of BRAFi, there are questions remaining to be answered to enable more efficient use of BRAFi in cancer therapy.